Music for autism: a protocol for an international randomized crossover trial on music therapy for children with autism - Ruiz, Marianna; Groessing, Alexander; Guran, Alexandrina; Koçan, Asena U.; Mikus, Nace; Nater, Urs M.; Kouwer, Karlijn; Posserud, Maj-Britt; Salomon-Gimmon, Maayan; Todorova, Boryana; Wagner, Isabella C.; Gold, Christian; et al. (Frontiers in Psychiatry, 2023)
MR drafted the manuscript and finalized the version for submission. MR and AGr coordinated preparations for recruitment, assessments, and interventions. AGu designed the behavioral music prediction tasks and AUK oversaw their use. UMN advised on hair cortisol methods. KK advised on neuroimaging data analysis. NM designed the behavioral action prediction tasks. MBP advised on clinical assessments and potential sites for recruitment of participants. MSG designed strategies for ensuring and assessing treatment fidelity. ICW designed the microbiome data collection. CG, GS, and KS designed the study and supervised its conduct.